Experimental study of the buckling of a soft rod in a soft medium - Low, Jia Cheng (Nanyang Technological University, 2021)
Buckling is deemed as the deformation of a structure due to instability after being subjected to compressive axial forces that exceed the critical loading value. Buckling of columns have been extensively research on. However, for buckling of a soft rod in a soft medium it is a new approach of research. In this research project, the author will make use of food products to substitute as the soft rod and soft medium for the experiment and through analysing the experiment result, the author will be able to understand how much load does the soft rod withstand before buckling will occur. This experiment will allow the author to study the effect of the concentration of the soft medium on the buckling shape and also the critical buckling load of the soft rod embedded in the soft medium. The results will not only be applicable in engineering field of studies but also assist in the understanding of biological field where human body such as bones covered in muscles are similar to the setup of the experiment. This experiment will also allow the author to relate to the robotics field where robotics arms are also of similar layout which is very important as robotics are becoming extensively used in every day’s work. This Final Year Project will be focusing on setting up a test rig for the experiment and making use of ‘Hotdogs’ and also ‘Agar Agar’ as the ingredients for the experiment to simulates as a soft rod in a soft medium. Together with the parameters of different concentration of the soft medium, and also the length of the soft rod we will observe the final buckling shape and the critical buckling load of the soft rods. Observations will also be made on the original soft rod without a medium and comparison will be made to better understand the importance of a surrounding medium.